Extent of Knowledge of ATMA Beneficiaries and Non-beneficiaries Farmers towards Improved Wheat Cultivation Technology - Kumar, Arun; De, Dipak (Indian Journal of Extension Education, 2016)
The study was conducted in Arazilines and Kashividyapeeth block of Varanasi distract of Uttar Pradesh to identify the  impact of ATMAtraining programme on extent of knowledge about improved wheat cultivation technologies. 120 trained  and 120 untrained farmers were selected trough PPS technique for study. 60.83 per cent trained farmers were in medium  knowledge level regarding improved wheat cultivation technologies. Besides 20.83 per cent and 18.33 per cent untrained  farmers were in low and high knowledge level respectively. While in case of untrained farmers 70.83 per cent were in  medium knowledge level regarding improved wheat cultivation technologies. Besides 20.83 per cent and 8.33 per cent  untrained farmers were in low and high knowledge level respectively. The study revealed that trained farmers had higher  extent of knowledge of about improved wheat cultivation technologies than untrained farmers.
Keywords: Extent; knowledge; ATMA